Documentation of some changes in policy and practice that may have effects on the standard and outcome of medical education in Bangladesh after liberation - Yunus, Emran Bin (Journal of Chittagong Medical College Teachers’ Association, 2009)
doi: 10.3329/jcmcta.v18i2.3836 Journal of Chittagong Medical College Teachers' Association 2007: 18(2):43-46